2007
DOI: 10.1111/j.1600-0404.2007.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional arousal enhances declarative memory in patients with Alzheimer’s disease

Abstract: We demonstrated that an emotionally arousing content enhances long-term declarative memory in AD. Furthermore, present finding supports the use of this instrument for clinical and research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
(46 reference statements)
5
23
0
2
Order By: Relevance
“…These findings support the latter hypothesis, that memory for emotionally significant material, such as distress in the family member who acts as the main carer, may remain relatively intact in people with dementia. This finding is compatible with the work of Hamann et al (1997), Kazui et al (2000), and Satler et al (2007), who showed that the emotional arousal caused by emotionally significant material enhances memory in people with cognitive impairment.…”
Section: Discussionsupporting
confidence: 94%
“…These findings support the latter hypothesis, that memory for emotionally significant material, such as distress in the family member who acts as the main carer, may remain relatively intact in people with dementia. This finding is compatible with the work of Hamann et al (1997), Kazui et al (2000), and Satler et al (2007), who showed that the emotional arousal caused by emotionally significant material enhances memory in people with cognitive impairment.…”
Section: Discussionsupporting
confidence: 94%
“…This result, which corresponds to intact emotional information processing in aging and AD, is in parallel with previous research [5,25,29,30,43]. The EEM effect was present for the recall of pictures and the pattern was similar in the groups: emotionally valenced (both pleasant and unpleasant) pictures were remembered more than neutral ones.…”
Section: Discussionsupporting
confidence: 80%
“…Others demonstrated different EEM patterns for word recall [24] and for picture recall [25] in AD. In some studies, EEM was in favour of unpleasant stimuli [24,26,27,28,29] while others showed an enhancement for pleasant stimuli [25,30]. These conflicting results are probably due to different methodologies.…”
Section: Introductionmentioning
confidence: 83%
“…For instance, Kazui et al [18] used a story paradigm in which AD patients heard a neutral story and an emotional story describing a child badly hurt in an automobile accident; recall was better for the emotional than for the neutral story. This pattern was confirmed by Satler et al, [19] who exposed AD patients to a neutral and an emotional story describing a medical operation of a child after a bad car accident. When answering a questionnaire about the stories, AD participants showed better memory for the emotional than for the neutral story.…”
Section: Introductionmentioning
confidence: 56%